Polarographic Determination of Metronidazole - Siva Sankar, P.; Jayarama Reddy, S. (Asian Journal of Chemistry, 2010)
The advanced electrochemical technique, differential pulse polarography is used to develop analytical procedure for the determination of metronidazole in buffered aqueous media. The procedure described has been used for the determination of metronidazole in different tablet formulations without any prior separation.